2020
DOI: 10.15252/embj.2019102539
|View full text |Cite
|
Sign up to set email alerts
|

Tollip coordinates Parkin‐dependent trafficking of mitochondrial‐derived vesicles

Abstract: Multiple mitochondrial quality control pathways exist to maintain the health of mitochondria and ensure cell homeostasis. Here, we investigate the role of the endosomal adaptor Tollip during the mitochondrial stress response and identify its interaction and colocalisation with the Parkinson's disease-associated E3 ubiquitin ligase Parkin. The interaction between Tollip and Parkin is dependent on the ubiquitin-binding CUE domain of Tollip, but independent of Tom1 and mitophagy. Interestingly, this interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 85 publications
0
58
0
Order By: Relevance
“…and Parkin for their biogenesis [6][7] , although Parkin may be required for their endosomal delivery 8 . In macrophages, bacterial infection triggers the PINK1/Parkin-dependent formation of Sod2positive/Tom20 negative MDVs that traffic to the phagosome to generate anti-microbial hydrogen peroxide 9 .…”
Section: Introductionmentioning
confidence: 99%
“…and Parkin for their biogenesis [6][7] , although Parkin may be required for their endosomal delivery 8 . In macrophages, bacterial infection triggers the PINK1/Parkin-dependent formation of Sod2positive/Tom20 negative MDVs that traffic to the phagosome to generate anti-microbial hydrogen peroxide 9 .…”
Section: Introductionmentioning
confidence: 99%
“…We observed the regulatory roles of PIAS4 and SENP3 are abrogated in TOLLIP depletion cells and revealed that cargo receptor TOLLIP arrests ACE2 to deliver it to autophagosome for subsequent degradation. TOLLIP has also been shown to facilitate endosomal organization and cargo tra cking, dependent on an association with the ubiquitylated cargo receptor p62 and the ubiquitin E3 ligase RNF26, indicating a potentially important function for TOLLIP in directing ubiquitylation of E3 substrates or their subsequent tra cking 24,31 . Our data indicate that a TOLLIP-ACE2 interaction is dependent on the TOLLIP CUE domain, but is not perturbed by a defect in the membrane recruitment, and TOLLIP delivers the K48-linked ubiquitylated ACE2 to autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…5b). To further elucidate the mechanism of ACE2 recognition, we generated TOLLIP R78A or M240A/F241A, L267A/L268A (CUE domain mutant) constructs, which inhibit the binding of TOLLIP to phosphatidylinositol 3-phosphate (PI3P) and PI(4,5)P 2 or ubiquitin, respectively 23,24 . Since TOLLIP CUE mutants cannot interact with ACE2 (Fig.…”
Section: Sumoylation Deceases the K48-linked Ubiquitination Of Ace2mentioning
confidence: 99%
“…As an ESCRT-0 component, TOM1 interacts with TOLLIP, Endofin, ubiquitin, and clathrin ( Table 1; Yamakami et al, 2003;Katoh et al, 2004Katoh et al, , 2006Seet et al, 2004;Seet and Hong, 2005;Xiao et al, 2015) and transports cargo, as demonstrated by its role in trafficking the delta opioid receptor (Lobingier et al, 2017), interleukin 1-receptor, type 1 (IL-1R1) (Brissoni et al, 2006), and the cargo within mitochondrial-derived vesicles ( Table 2; Ryan et al, 2020). TOM1 and TOM1-L1 also interface with the ESCRT-I tumor susceptibility gene 101 protein in Dictyostelium (Blanc et al, 2009) and humans (Puertollano, 2005), respectively ( Table 2).…”
Section: Tom1 and The Endosomal Ubiquitin-dependent Sorting Pathwaymentioning
confidence: 99%
“…Thus, the presence of several ubiquitin-binding domains in ESCRT proteins may contribute to an increase in the overall affinity for cargo for an efficient sorting process. TOM1, in coordination with TOLLIP, promotes the lysosomal degradation of IL-1R1 (Brissoni et al, 2006) and the cargo within mitochondrial-derived vesicles (Ryan et al, 2020; Table 2). TOLLIP is also modular with an N-terminal TOM1 binding domain (TBD) (Yamakami et al, 2003), a central PtdIns3P-binding conserved 2 (C2) domain (Ankem et al, 2011), and a C-terminal coupling of ubiquitin to endoplasmic reticulum degradation (CUE) domain (Azurmendi et al, 2010).…”
Section: Tom1 and The Endosomal Ubiquitin-dependent Sorting Pathwaymentioning
confidence: 99%